RECRUITMENT, TRAINING, TECHNOLOGY, AND EMPLOYEE ENGAGEMENT STRATEGIES IN CREATING HUMAN CAPITAL PERFORMANCE THROUGH AN INNOVATIVE WORK SYSTEM - Suwandi Suwandi; Mei Rani Amalia; Agnes Dwita Susilawati (SOSIOEDUKASI, 2026)
In the era of digital transformation and globalization, organizations are required to develop innovative human resource management strategies to maintain sustainable competitiveness. Human capital performance increasingly depends on the effective integration of recruitment, training, technology, and employee engagement within an innovative work system. This study aims to analyze how these four strategic components interact to enhance human capital performance in contemporary organizations. The research adopts a qualitative approach using a literature review method by examining relevant national and international academic publications published between 2015 and 2025. Data were collected through a systematic literature review process involving keyword identification, database searching, article selection, and thematic categorization. The data analysis employed thematic content analysis to identify recurring patterns and conceptual relationships among recruitment strategies, training and development, HR technology, employee engagement, and innovative work systems. The findings reveal that strategic recruitment supported by digital technologies improves alignment between employee competencies and organizational goals, while continuous training strengthens employee adaptability and innovative capacity. HR technology serves as an integrative infrastructure that connects recruitment, training, and engagement processes, whereas employee engagement functions as a key mediator in maximizing performance outcomes. Overall, the study concludes that a holistic and integrated innovative work system significantly enhances human capital performance and supports organizational sustainability in the digital era.